1990
DOI: 10.1097/00006123-199003000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid-pleural and subarachnoid-mediastinal fistulae

Abstract: Subarachnoid-pleural fistula and subarachnoid-mediastinal fistula are rare complications of chest trauma. One case each of subarachnoid-mediastinal fistula and subarachnoid-pleural fistula is described. Both patients were young children who suffered severe longitudinal distraction injuries to their thoracic spine and exhibited complete cord transection without radiographic evidence of vertebral column injury. Progressive mediastinal widening and enlarging pleural effusion in the absence of angiographic evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Development of a subarachnoid-pleural fistula has also been reported after thoracotomy for lung, chest wall, and spinal tumors, when an iatrogenic meningeal laceration results in establishing communication between the spinal subarachnoid space and the pleural cavity. 1,4,5,12 In our case, a combination of traumatic and iatrogenic factors was at play. Vertebral body fragments that were retropulsed into the spinal canal presumably caused a dural laceration.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Development of a subarachnoid-pleural fistula has also been reported after thoracotomy for lung, chest wall, and spinal tumors, when an iatrogenic meningeal laceration results in establishing communication between the spinal subarachnoid space and the pleural cavity. 1,4,5,12 In our case, a combination of traumatic and iatrogenic factors was at play. Vertebral body fragments that were retropulsed into the spinal canal presumably caused a dural laceration.…”
Section: Discussionmentioning
confidence: 57%
“…In a review of 24 patients with these fistulas, the authors found conservative treatment to be ineffective in all but one patient; 16 patients ultimately required surgical exploration for direct repair of the fistula. 12 Traumatic injury can result in subarachnoid-pleural fistula if the thoracic spine dura and the parietal pleura are both breached, thus allowing CSF to enter and accumulate in the pleural cavity. 2,3,6,11,13,14 These cases are frequently associated with a complete spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CT myelography can provide a better anatomical picture, it may have an increased incidence of false-negative results. 10,15,19,[23][24][25] We recommend a nuclear study as the initial investigation because it is more sensitive, and this should be followed by CT myelography, if necessary, to define further the anatomical details of the fistula. As indicated in the aforedecribed case in which there was no objective evidence of an SPF despite symptoms and signs consistent with one, an objective study such as nuclear cisternography is important to verify the diagnosis before committing a patient to repeated operation.…”
Section: Discussionmentioning
confidence: 99%